"When I first saw a condom, I was frightened": A qualitative study of sexual behavior, love and life of young cross-border migrants in urban Chiang Mai, Thailand - Arunrat Tangmunkongvorakul (2018)
© 2017 Tangmunkongvorakul et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background: Many young migrant workers move across the border to Chiang Mai, a major city in Northern Thailand, in search of work opportunities. This study describes their sexual behavior, lifestyles, relationships and experiences with youth-friendly sexual and reproductive health (SRH) services. Methods: This is the qualitative arm of a mixed methods study using focus group discussions (FGDs) among young MWs aged 15–24 years in urban Chiang Mai. We conducted 6 FGDs with 84 participants (43 males, 41 females) organized in groups of 10–15 people, including 3 groups of males, 2 groups of females, and 1 group of both males and females. Results: We found that the lack of parental control, pressure to assimilate into Thai society, access to social media and modern communication technologies, and limited knowledge and access to sexual and reproductive health (SRH) services interplayed to shape lifestyle and sexual behaviors, including low condom use among young migrants. Conclusion: The present study helped discern the vulnerability of young migrants to adverse SRH outcomes. This particular group of youth needs urgent intervention to improve their knowledge on SRH and access to a youth-friendly clinic to help them personalize risk of HIV and other adverse SRH outcomes.